Primary malignant neoplasms of the cecal appendix: unusual findings in acute appendicitis - Carlotto, Fernanda Marcante; Garcia, Julia Carolina; Correa, Nathalia Beck; Neto, Marcos Dal Vesco; Stolfo, Josiane Borges; Schmitz, Lucas Duda; Dal Vesco, Juarez Antonio; Carlotto, Jorge Roberto Marcante (Clinical and Biomedical Research, 2021)
Introduction: To evaluate the prevalence of appendix neoplasia correlating with patient profile, histological types and frequency. Methods: Data collection was performed in the Pathology Department of a General Hospital, with the objective of identifying patients diagnosed with malignant cecal appendix tumors by histopathologic study of specimens from acute appendicitis. Results: The prevalence of malignant primary epithelial neoplasia of the appendix was 1%. Fifty percent of the cases were neuroendocrine tumors, 35% were mucinous, and 15% were adenocarcinomas. The mean age at diagnosis was 41.3 (SD, 20.4) years (range16-81), with a women/men ratio of 3:1. Discussion: Appendiceal neoplasms are rare and should be suspected manly in women over 40 years of age with suggestive symptoms of acute appendicitis. The size, location, extent, margins and presence of mucin are essential findings for the treatment of these patients.